Valuing Environmental Damage as State Financial Loss in Corruption Cases: A Substantive Justice Analysis of The Harvey Moeis Verdicts - Laily Maghfiroh; Abdul Kholiq (MASI Mandiri Edukasi, 2025)
This study examines the regulatory framework for assessing environmental damage as a basis for establishing state financial losses in corruption cases and analyzes judicial reasoning in sentencing to realize substantive justice. It addresses a key gap in Indonesian legal practice: the absence of an integrated framework linking environmental damage valuation to state loss calculations, and the limited inclusion of ecological restoration costs in criminal sanctions. The research employs a normative juridical method, drawing on legislative, conceptual, case-based, and comparative approaches, supported by primary, secondary, and tertiary legal materials. Data were obtained through a literature review and limited structured interviews with environmental law experts and practitioners. Within the normative juridical framework, the interviews serve solely as supplementary secondary data to complement and confirm the normative analysis of statutory regulations, particularly to verify the adequacy and practical applicability of the legal framework governing environmental damage assessment and state financial loss calculation. Legal materials were analyzed using qualitative descriptive analysis. The findings indicate that environmental damage calculations rely on ecological components regulated under the Environmental Protection and Management Law, Ministry of Environment Regulation No. 7 of 2014, and Government Regulation No. 22 of 2021. In the sentencing of Harvey Moeis and Nur Alam, judges emphasized abuse of authority, official position, degree of culpability, and motive; however, ecological restoration costs were not systematically integrated into sentencing, thereby constraining the realization of substantive justice. This study recommends adopting a unified guideline linking environmental damage valuation to state financial losses and mandating the incorporation of environmental restoration obligations into criminal sentencing. The research is limited to two court decisions and does not include a broader empirical analysis of sentencing patterns.